2018
DOI: 10.3389/fpsyg.2018.01864
|View full text |Cite
|
Sign up to set email alerts
|

How Working Memory Provides Representational Change During Insight Problem Solving

Abstract: Numerous studies of insight problem solving are focused on both the control and storage systems of working memory. We obtained contradictory data about how working memory systems are involved in insight problem solving process. We argue that measuring the dynamics of the control system and storage systems through the course of problem solving can provide a more refined view on the processes involved, as a whole, and explain the existing controversies. We theorize that specific insight mechanisms require varyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 41 publications
2
14
0
1
Order By: Relevance
“…Given the lack of previous studies using a dual-task paradigm with the CRAT to study insight and using generalized linear mixed models analyses, we used the average effect size found in previous dual-task studies on insight to make a well-informed estimate of our required sample size. In previous dual-task studies, an average cohen's d effect size has been reported of .68 for solution time on the secondary task and .62 for the number of correctly solved problems as a function of solution type and working memory load (Korovkin et al, 2018;Lavric et al, 2000). Regarding solution accuracy and solution confidence, we could not extract cohen's d effect sizes due to a lack of previous data.…”
Section: Participantsmentioning
confidence: 84%
See 1 more Smart Citation
“…Given the lack of previous studies using a dual-task paradigm with the CRAT to study insight and using generalized linear mixed models analyses, we used the average effect size found in previous dual-task studies on insight to make a well-informed estimate of our required sample size. In previous dual-task studies, an average cohen's d effect size has been reported of .68 for solution time on the secondary task and .62 for the number of correctly solved problems as a function of solution type and working memory load (Korovkin et al, 2018;Lavric et al, 2000). Regarding solution accuracy and solution confidence, we could not extract cohen's d effect sizes due to a lack of previous data.…”
Section: Participantsmentioning
confidence: 84%
“…Recent insight theorists (Bowden & Grunewald, 2018;Weisberg, 2015) have argued that each solution type involves both processes (Type 1 and 2) to some extent. Therefore, implementing a more demanding WM load may unravel if both solution types can be affected by WM load, albeit to a different extent (insight potentially less than non-insight; see Korovkin et al, 2018, for an example).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the Hi-AVH group with insight, the Hi-AVH group without insight showed greater disturbance within these networks, and also within components of mood regulation circuitry. Previous studies have reported that functional alterations in these circuits are not only related to AVH but also to insight (Webb et al 2016 ; Korovkin et al 2018 ; Hill and Kemp 2018 ; Belvederi Murri et al 2016 ; Tik et al 2018 ; Sapara et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Frisco, Sanne, Kroesbergen, & Johannes (2013) conducted a research in elementary school and found that all components of working memory were related to mathematical performance, especially verbal updating. Korovkin (2018) investigated the dynamics of working memory systems during problem solving. He stated that the functioning memory storage was needed when solving a problem and just before finding the solution the control system played an important role.…”
Section: Introductionmentioning
confidence: 99%